Health services residues: Environmental responsibility in Primary Care Professional view (Research, Society and Development, 2021)
This study aimed to analyze the professionals knowledge of Primary Health about the responsibility of the health services waste production until the release to the environment. This is an exploratory-descriptive and cross- sectional study using a qualitative approach, carried out in 36 Basic Health Units present in nine health districts of the Campina Grande city in the state of Paraiba. The study sample was composed by seven doctors, 24 nurses, 04 dentists, 16 nurse assistants, 04 oral health auxiliaries, totaling 55 professionals interviewed. Data were collected from august 2011 to january 2012 and analyzed in the light of the Bardin (2016) postulates. The results showed clearly that professionals make an association between inadequate waste management to environmental contamination and the onset of diseases. Other question referred was the lack of information on waste management; inadequate work conditions; lack of support for professionals victims of accidents with waste. The interviewees also indicated the selective waste collection as an alternative to improve the management of residues. Thus, it can be concluded that the study can be of great value to managers who wish to make changes in the collection of waste from health services.